Humanin peptide ameliorates reproductive dysfunction and restores neuroendocrine mechanisms in SSRI-treated male rats - Akipek, Rumeysa Esra Kom; Ercan, Eda Coban; Akipek, Mehmet Emre; Atmaca, Ahmet Tuluhan; Ozdede, Mehmet Ridvan; Turk, Gaffari; Canpolat, Sinan (Elsevier, 2026)
Selective serotonin reuptake inhibitors (SSRIs) such as paroxetine frequently induce male sexual dysfunction by disrupting neuroendocrine balance and central dopaminergic pathways. This study investigated whether humanin, a mitochondria-derived peptide, could mitigate paroxetine-induced reproductive and behavioral impairments in male Sprague-Dawley rats. In Phase 1, fifty rats were randomized into control, sham, paroxetine (20 mg/kg/day via oral gavage), humanin (1 mg/kg/day via subcutaneous infusion), and paroxetine + humanin groups (n = 10/group) to evaluate sexual behavior, sperm quality, serum hormones, and dopaminergic activity within the nucleus accumbens (NAc) and medial preoptic area (MPOA). In Phase 2, central neurochemical dynamics in a separate cohort of healthy rats (n = 8) were assessed using in vivo microdialysis coupled with HPLC-ECD to measure extracellular dopamine and its metabolites in the NAc. Paroxetine significantly impaired sexual motivation and performance, reduced sperm motility, concentration, and mitochondrial membrane potential, elevated prolactin, and suppressed testosterone, luteinizing hormone, and dopamine levels in both the NAc and MPOA (p < 0.05). Humanin co-administration significantly reversed these adverse effects, restoring ejaculatory frequency, copulatory efficiency, sperm parameters, and hormonal balance. Furthermore, humanin counteracted the paroxetine-induced dopaminergic suppression in the MPOA and NAc, while acute microdialysis revealed a supportive upward trend in dopamine turnover under basal conditions. These findings demonstrate that humanin exerts potent pro-fertility and neuroprotective effects against antidepressant-induced sexual dysfunction. By preserving mitochondrial integrity and modulating central dopaminergic and neuroendocrine circuits, humanin emerges as a promising therapeutic agent for preserving male reproductive health during SSRI treatment.
Keywords: Humanin; Ssri; Male Sexual Dysfunction; Rats